HUBUNGAN MEDIA AUDIO VISUAL ROKAT TASE’ TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS IV DI SDN MANDUNG 03 BANGKALAN - Siti Fatimatus Zahroh; Budi Purwantiningsih; Solchan Ghozali (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
This research uses a quantitative approach, This type of research uses a type of experimental research, starting from February 1 to May 28, 2022 at SDN Mandung 03, located in Mandung Village, Kokop District, Bangkalan Regency, East Java. The time of this study was carried out in May face-to-face. The independent variable in this study is audio-visual media rokat tase' and the variable tied to this study is student learning outcomes. There is an influence on student learning outcomes Based on the results of correlation analysis using the pearson correlation test with the help of windows 26 it can be seen that the significance value for audio-visual media rokat tase' and learning outcomes less than is 0.000 less than 0.05 (0.000<0.05), this is in accordance with the correlation interpretation guideline table 0.978 is in the interval 0.80-1.000, which shows a correlation